Formation of management and technological maturity levels of enterprises for their dynamic development - Shpak Nestor; Vytvytska Olga; Martynyuk Olena; Kylaec Maria; Sroka Włodzimierz (Engineering Management in Production and Services, 2022)
Currently, the market environment contains many factors influencing the enterprise’s competitiveness. Instability, the unpredictability of events, and insufficiently effective functioning of market mechanisms alter the management focus and processes engaged in an enterprise’s functioning. Some of them are intensive in terms of required resources and finance. Such a dynamic situation requires the enterprise management to build innovative solutions to flexibly respond and timely adapt to change. Therefore, this study aims to develop theoretical and applied approaches to determining the level of managerial and technological maturity of the basic set of technologies implemented in enterprises. In the context of this issue’s development and aiming to achieve the purpose, the study proposed a model approach where the introduction of individual technologies allows combining the rules for determining the enterprise’s management and the technological maturity level, i.e., its readiness for such changes. The construction of the model was based on the analysis and calculation of statistical data from four groups of technologies (corporate, industrial, decision support, and information technologies, which are divided into subclasses) and based on the theory of dynamic innovation development. The results were tested at seven food industry enterprises in Ukraine. Based on the study, the actual level of managerial and technological maturity of enterprises was determined, creating one complex set of technologies that depend on the level and structural changes in management and the level of technological maturity of enterprises. It can be used as a typical model for differently sized enterprises representing various industries.